Volatile memory - Haddon, Seth (Tor Publishing Group, 2025)
"This is How You Lose the Time War meets Ex Machina: Seth Haddon's science fiction debut, Volatile Memory, is a sapphic sci-fi action adventure novella. With nothing but a limping ship and an outdated mask to her name, Wylla needs a big pay day. When the alert goes out that a lucrative piece of tech lies hidden on a nearby planet, she calls on all the swiftness of her prey-animal instincts to beat other hunters to it. What you found wasn't your ticket out-it was my corpse wearing an AI mask. When you touched the mask, you heard my voice. A consciousness spinning through metal and circuits, a bodiless mind, spun to life in the HAWK's temporary storage. I crystallized and realized: I was alive. Masks aren't supposed to retain memory, much less identity, but the woman inside the MARK I HAWK is real, and she sees Wylla in a way no one ever has. Sees her, and doesn't find her wanting or unwhole. Armed with military-grade tech and a lifetime of staying one step ahead of the hunters, Wylla and HAWK set off to get answers from the man who discarded HAWK once before: her ex-husband"-- Provided by publisher.